Diseño del balance Score Card para la empresa del sector de producción y comercialización de alimentos (2023)
The lack of basic and elementary knowledge within organizations is one of the main factors that are experienced daily and that reflects the negative effect during the future process of the same, this is largely directed at the lack of organization led by management and detaching itself from the other areas that make up the appropriate procedure within the organization, repressing improvement and the search for optimal results in order to generate better profitability and adequate decision making, considering success, positioning and recognition in the market.